Rebuilding lives after the Tsunami: exploring the livelihood status of BRAC's beneficiaries in Sri Lanka - Sulaiman, Munshi (BRAC, 2019)
BRAC Sri Lanka started rehabilitation and livelihood support programme for the tsunami-affected people about 6 months after the disaster. Though the programme components include a range of rehabilitation and livelihood supports, this study focused only on the grant and loan receivers. The study finds some evidences of effective targeting by the programme. There is also evidence of programme impact on the beneficiaries' income and assets. Length or participation in the programme has positive associations with the income and assets of the beneficiaries. However, the associations arc more obvious tor the grant receivers than the loan receivers. The loan programmes were initiated at a later stage once the 'grant phase' was over. Since it usually takes a few loan cycles to show a clear impact on income and assets. the proper assessment of borrowing should wait tor two more years. BRAC's loan programme in Sri Lanka seems to have a very good prospect of flourishing further.